Wheat genotype responses to phosphorus and zinc: Differential growth, mycorrhizal interactions, and zinc accumulation - Ali, Amanat; Depar, Nizamuddin; Panhwar, Qurban Ali; Irfan, Muhammad (Mehran University research journal of engineering and technology, 2025)
Agronomic methods for increasing wheat's grain zinc (Zn) content have been found to be an effective means of preventing human zinc deficiency. To assess the response of three wheat genotypes to varying quantities of phosphate (P) and zinc (Zn) for grain yield and Zn accumulation, a pot study was conducted. Using a completely randomized design (CRD) factorial combination, two Zn levels (0, 5 kg ha-1) and three P levels (0, 90, 120 kg ha-1) were applied. The study revealed that wheat genotypes responded differently to varied doses of P and Zn. In order to considerably increase yield (grain and straw) and related features (number of spikelets per spike, spike length, number of grains per spike, and 1000-grain weight), the combination of 5 kg Zn and 90 kg P ha-1 was used. The most effective combination for all wheat genotypes was found to be 5 kg Zn + 90 kg P ha-1, which significantly increased grain yield (23 %) and related attributes including number of spikelets per spike (11 %), spike length (10 %), number of grains per spike (17%) and 1000-grain weight (10 %) as compared to control. In general, all wheat genotypes showed decreased mycorrhizal root infection (205-290 %) and grain zinc uptake (22-45 %) when exposed to a higher dose of P (120 kg ha-1) and vice versa. The genotype TD-1 had the higher agronomic Zn efficiency (139 % and 235 %) at 5 and 90 kg Zn and P ha-1 as compared to other genotypes NIA-WR1 and Chakwal-86 respectively. Similarly, it was proved that applying 5 kg of Zn ha-1 along with P level of 90 kg ha-1 was the best combination to maximize the potential yield of Chakwal-86. Among the genotypes, NIA-WR1 accumulated the higher quantity of Zn (51 % and 40 %) in its grains at 5 kg Zn along with 90 kg P ha-1 compared to the genotypes TD-1 and Chakwal-86 respectively. The same genotype, NIA-WR1 accumulated the maximum Zn (44.26 µg g?¹) in its grains even without the application of exogenous Zn. This indicates that it is Zn-efficient and capable of thriving in Zn-deficient soils. It can utilize the Zn present in the native soil to achieve a high zinc content in its grains. However, further research is needed before general recommendations can be made for wheat growers.